"Change is what can actually make the tough times better": A patient‐centred patient safety intervention delivered in collaboration with hospital volunteers. (21st October 2018) - Louch, Gemma; Mohammed, Mohammed A.; Hughes, Lesley; O'Hara, Jane
Abstract: Background: The PRASE (Patient Reporting and Action for a Safe Environment) intervention provides a way to systematically collect patient feedback to support service improvement. To provide a sustainable mechanism for the PRASE intervention, a 2‐year improvement project explored the potential for hospital volunteers to facilitate the collection of PRASE feedback. Objective: To explore the implementation of the PRASE intervention delivered in collaboration with hospital volunteers from the perspectives of key stakeholders. Design: A qualitative case study design was utilized across three acute NHS trusts in the United Kingdom between March 2016 and October 2016. Ward level data (staff interviews; action planning meeting recordings; implementation fidelity information) were analysed taking a pen portrait approach. We also carried out focus groups with hospital volunteers and interviews with voluntary services/patient experience staff, which were analysed thematically. Results: Whilst most ward staff reported feeling engaged with the intervention, there were discordant views on its use and usefulness. The hospital volunteers were positive about their involvement, and on some wards, worked with staff to produce actions to improve services. The voluntary services/patient experience staff participants emphasised the need for PRASE to sit within an organisations' wider governance structure. Conclusion: From the perspective of key stakeholders, hospital volunteers facilitating the collection of PRASE feedback is a feasible means of implementing the PRASE intervention. However, the variability around ward staff being able to use the feedback to make changes to services demonstrates that it is this latter part of the PRASE intervention cycle that is more problematic.